a) -y+8x-z-2x dla x= -2, y=6, z=3
-6+8*(-2)-3-2*(-2) = -6 - 16 - 3 + 4= -21
b) -8y-4z+x-y-2+1 dla x=-0,5, y= -1, z=2
-8*(-1) - 4*2 + (-0,5) - (-1) - 2 + 1 = 8 - 8 - 0,5 + 1 -2 + 1 = -0,5
c) 9y-(-7y+x) +(6x-7y) dla x= -2, y =3
9*3 - (-7*3 + (-2)) + (6*(-2) - 7*3) = 27 - (-21 -2) + (-12 -21) = 27 - (-23) + (-33) =
= 27 + 23 - 33 = 17
d) (6a-8b-0,7)-(6,9+a-5b)+ 1,8 dla a=0,2, b=0,1
(6*0,2 - 8*0,1 - 0,7) - (6,9 + 0,2 - 5*0,1) + 1,8 = (1,2 - 0,8 -0,7) - (6,9+0,2-0,5) +1,8 = (-0,3) - 6,6 + 1,8 = -0,3 - 6,6 + 1,8 = -5,1